Empırıcal Evıdence On The Performance Of Technology Sector Companıes In Asean Countrıes - Saipul A. Muhsyaf; Siti Atikah; Susi R. Cahyaningtyas; Rahmi S Ramadhani (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Internet use is an indicator of sustainable economic development. The internet has become an important tool for people to obtain the information they need. Internet use has increased during the Covid-19 pandemic. Increased internet use should encourage increased demand for hardware and software. Indirectly, this can encourage sales growth and company performance that supports the implementation of information technology. This research examines the association between company profitability and the market performance of technology sector companies on the Stock Exchanges of 6 ASEAN member countries. Data is obtained through the stock exchanges of each country as well as through other data sources. The research year in the analysis is divided into 2 periods, 2017-2019 and 2020-2021, and is treated as an independent variable along with profitability. The dependent variable is company performance. Data were analyzed using multiple linear regression. The test results show that profitability as measured using Return on Assets (ROA) has a positive effect on company performance. Firm performance in this study is measured by abnormal return (AR). This research also analyzes AR in the period before and after the Covid-19 pandemic. The test results show that AR in the period before the Covid-19 pandemic was lower than in the period after or during the Covid-19 pandemic. This research replicates previous research regarding the influence of profitability on company performance but adds the dichotomous variable year (dyear) and the form or system of government in the country being observed (dform).